Service-Learning as a niche innovation in higher education for sustainability - Álvarez-Vanegas, Alejandro; Ramani, Shyama V.; Volante, Louis (Frontiers in Education, 2024)
Education for Sustainable Development (ESD) is a framework proposed by UNESCO to develop knowledge, skills, values, and behaviours in youth for sustainable development. As part of the global development agenda, higher educational institutions are expected to integrate ESD into their curricula. Service-Learning is a type of experiential learning in which students combine academic coursework with community service which is aligned with the learning objectives of their academic program. Within this global context, this paper examines how universities are responding to this call through the introduction of Service-Learning. In light of the global trend, our paper investigates how universities are responding to this call through the introduction of Service-Learning programs. First, a comprehensive review of UN documents presents the background and structure of ESD. Second, a systematic review of the academic literature analyses how service-learning is being introduced in higher educational institutes. Key findings are that serviceService-learning Learning programs align with most of the UNESCO framework components, but higher education institutions are finding it challenging to implement itthem. Educators play a pivotal role in implementation, and unless they are trained and incentivized and this is systematized, not only serviceService-learning Learning but also ESD may fail to transform learning environments. Furthermore, there is a need for impact evaluation, particularly in terms of key sustainability competences. The three major challenges are insufficient educator capacity, funding, and educator attitudes. These challenges can be addressed through university-based projects addressing local problems that have a visible impact, as well as collaboration with local communities, other institutions and, social enterprises.